In Search of a Regime of Limited Liability in Malaysian Partnerships - Abd Ghadas, Zuhairah Ariff (2002)
For many years, partnership has been the oldest and the most basic entity choice which combines the efforts of more than one individual. As commerce progresses, partnership has to compete with other business entities, especially the company which gains much favour due to the advantage of limited liability. Being an unincorporated business association, partnership applies the principle of unlimited liability whereby partners are jointly and personally liable for partnership obligations to the extent they exceed the assets of the partnership. The principle of unlimited liability in partnership is constantly criticized as it imposes heavy obligations and high business risks upon the partners. However, despite the disadvantages it carries, the principle of unlimited liability in partnership is neither replaced nor modified. Instead, the partnership laws are expanded to include alternatives, such as limited partnerships and limited liability partnerships, which provide the advantages of limited liability to the partners. The practice of limited partnerships and limited liability partnerships is already recognized and widely accepted in developed countries such as the United States of America, the United Kingdom of Great Britain and Northern Ireland, France and Germany. In Malaysia, the practice of partnership is still confined to general partnerships. There is neither development nor major amendment being made to the existing partnership laws. The latest development in Malaysian partnership laws was seen in Labuan when the Labuan Offshore Limited Partnership Act 1997 was passed to allow limited partnership to be practised in the Island. With the development and expansion of partnership laws that allows limited liability to be practised in a partnership, it is high time for Malaysia to look at these alternatives as one of the means to expand business options and increase investments in this country. Nonetheless, in proposing the practice of limited liability in partnerships, there are many aspects which need to be clarified, such as the entity of the firm, the extent of limited liability which a partner has, the effect on partners' and third parties' rights and also the dividing line which differentiates a partnership with limited liability from a limited liability company. With the above queries and concern in mind, it is the aim of this thesis to clarify the legal aspects of partnerships in the search of the application of limited liability in Malaysian partnerships.